Green fire - Mallmann, Francis; Kaminsky, Peter; Gelb, Donna (Artisan, a division of Workman Publishing Co. Inc., 2022)
"Francis Mallmann is an Argentine grill master. Author of Seven Fires and Mallmann on Fire, he is known for his primal style of live-fire meat cookery-and until recently, he treated vegetables as a condiment or side dish. Now, in the highly anticipated The Green Fire, Mallmann shares his recipes and secrets for perfect grilled vegetables and fruits, creating dishes with the same elemental, rugged style for which he is world-renowned. With the goal of creating dishes that are better for our health and for the health of our planet, Mallmann uses the same live-fire techniques he has mastered in cooking meats to transform every vegetable into a dish as satisfying as a prime-cut steak. Pineapples are hung over a fire with butcher's twine, and beets are buried in its coals. Tomatoes are burnished on the cast-iron plancha to intensify their flavors. Whether slathered, seared, baked, blackened, or fried over the flames, Mallmann's fire-cooked vegetables are full of flavor and personality. Spring artichoke and fava salad, salt-baked beets with lemon confit, and cabbage steaks with a mustard-fennel crust are just a few of the stars. And desserts and cocktails are included, too! Evocative photos showcase the food, the fire, and Mallmann's magical setting in South America. The Green Fire is the book fans of Francis Mallmann's have been waiting for: the art of grilling with vegetables"--